2021
DOI: 10.1177/00139165211026607
|View full text |Cite
|
Sign up to set email alerts
|

Weather, Values, Capacity and Concern: Toward a Social-Cognitive Model of Specialty Crop Farmers’ Perceptions of Climate Change Risk

Abstract: As specialty crop production has become increasingly important to U.S. agriculture, public and private stakeholders have called for research and outreach efforts centered on risks posed by climate change. Drawing on a survey of specialty crop farmers, this study explores farmers’ perceptions of climate change risks. Underlying cognitive, experiential, and socio-cultural factors hypothesized to influence farmers’ climate change risk perceptions are tested using structural equation modeling techniques. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…In the CCRPM, the similarities and differences among the constituent elements were well-examined, and the survey items were prepared with sufficient consideration given to the heterogeneity among the components. A large sample of UK national (van der Linden, 2015 ) and nationwide (van Eck et al, 2020 ) studies have revealed that approximately 70% of the variance in climate change risk perception can be explained by this survey; this result has been replicated in multiple similar studies (Geiger et al, 2018 ; Xie et al, 2019 ; Han et al, 2022 ).…”
Section: Study 3: Examination Of the Construct Validity Of The Japane...mentioning
confidence: 59%
See 1 more Smart Citation
“…In the CCRPM, the similarities and differences among the constituent elements were well-examined, and the survey items were prepared with sufficient consideration given to the heterogeneity among the components. A large sample of UK national (van der Linden, 2015 ) and nationwide (van Eck et al, 2020 ) studies have revealed that approximately 70% of the variance in climate change risk perception can be explained by this survey; this result has been replicated in multiple similar studies (Geiger et al, 2018 ; Xie et al, 2019 ; Han et al, 2022 ).…”
Section: Study 3: Examination Of the Construct Validity Of The Japane...mentioning
confidence: 59%
“…First, to accurately discriminate and understand the concepts of knowingness, attitude, and behavior, we used van der Linden ( 2015 ) survey items instead of a questionnaire scale whose reliability and validity had been established. However, the results of van der Linden ( 2015 ) have been reproduced in many studies (Xie et al, 2019 ; Elshirbiny and Abrahamse, 2020 ; van Eck et al, 2020 ; Han et al, 2022 ); hence, it is also possible to be seen the reliability and validity have been sufficiently verified, even if no statistical indicators have been explicitly calculated. In addition, the van der Linden ( 2015 ) scale is specific to climate change in the environmental domain.…”
Section: Limitationmentioning
confidence: 94%
“…Greenhouse, hydroponics, and aquaponic systems claim to be more efficient and sustainable ways to produce food by using less inputs (water, pesticides, fertilizers). Adoption of these systems is on the rise in many urban centers as it is taken up by small and first-time growers [52]. It addresses food security in many areas and is a desirable choice for many small-scale and beginning farmers.…”
Section: Smart Sensors and The Internet Of Things (Iot)mentioning
confidence: 99%
“…Given that the prevailing culture in Chinese society is collectivism, especially in rural areas (Yandong Wang et al., 2019), others’ expectations lead to social pressure on farmers. Social influences have long been recognized as a crucial factor influencing decision‐making (Han et al., 2022; Singh et al., 2020). From this, we consider social influences to be an important aspect of environmental inputs.…”
Section: Literature Reviewmentioning
confidence: 99%